Steady-state analysis of power distribution system with dynamic charging electric vehicles - Wang, Chuan (Nanyang Technological University, 2020)
Increasing concerns about global carbon emission and the shortage of fossil fuels have shifted people’s attention from traditional cars towards electric vehicles (EVs). For EVs, charging is of great importance and can be largely classified into wireless and plug-in types. Wireless dynamic charging technologies are gradually replacing the plug-in ones as they allow EVs being charged while they are in motion. In this way, those EVs become a new type of loads - the moving loads. They may change their locations constantly in the network. A large number of EVs charging to the grid creates a significant challenge to the stability and quality of the overall power system, like affecting the voltage control. To analyze the steady-state problem of dynamic charging, voltage profiles along the distribution system and probabilistic load flow problems should be both considered.